EFFECTIVE TEACHING STRATEGIES AND APPROACHES IN A MULTIFACETED ONLINE PEDAGOGY LANDSCAPE IN AN ODEL INSTITUTION - Pule, Kereng Gilbert (Innovative Issues and Approaches in Social Sciences)
This qualitative case study explores the evolving landscape of a comprehensive Open Distance e-Learning (ODeL) institution, highlighting the complexities of online teaching and learning. This study uses an interpretive research paradigm, seeking to comprehend the views of instructors who are teaching online. The study involved six lecturers and six e-tutors who were purposively selected based on their online experience. Bronfenbrenner’s Ecological Systems Theory was selected as the theoretical model for this study as it presents an inclusive perspective on the various levels of impact that are likely going to shape the learning environment, which suits an online format. The results highlight that if technology is successfully integrated into online teaching with the bonus of a strong lecturer/e-tutor presence and weekly online lessons, student engagement and learning outcomes are significantly increased. In addition, lifelong learning and addressing the digital divide are essential to provide each student with equal education opportunities. The implications of the study are that ODeL institutions are required to constantly innovate and invest in both technological infrastructure and pedagogical training to try to meet the changing needs of students who now operate in a digital learning world.